Sex on the front: prostitution and venereal disease in Russia’s First World War - Hearne, Siobhan (Taylor & Francis, 2017)
Prostitution flourished during Russia’s First World War. Mass mobilisation and the displacement of millions of the empire’s population challenged the tsarist state’s ability to control both the movement and bodies of those buying and selling sex. In light of this, military and medical authorities shifted their attention more directly onto regulating men's bodies. Wartime social turmoil also increased the visibility of prostitution, which saw many enlisted men lament the apparent ‘moral decline’ that they witnessed on the front. This article examines how the tsarist authorities grappled to control the bodies of its populace on Russia's western front, and how the conflict had an impact upon ideas of morality and sexuality.